THE STUDY OF FIRST YEAR INTERNATIONAL STUDENTS’ EXPATRIATE EXPERIENCES IN UNIVERSITY OF MALAYSIA SABAH - Irma Wani Othman; Hasbullah Awang; Abu Bakar Abdul Hamid; Muhammad Safuan Yusoff; Herlina Jupiter (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Globalisation has a huge impact on the process of internationalisation of higher education to fulfil the country’s aspiration as a hub of higher education excellence globally alongside the effort of the Ministry of Higher Education in promoting Malaysia as one of the chosen destinations among international students. This research is based on two objectives that are (i) to identify the first year expatriation experience of international students in University Malaysia Sabah and (ii) to investigate the tendency of international students in gaining meaningful experiences during the stay in the chosen country. The discussion of this paperwork is based on the interviews done with 20 volunteered respondents who are also involved in focal group discussions. The research result shows most of the respondents chose University Malaysia Sabah as it is deemed to be a smart choice in relation to its status as a global and competitive university. Meanwhile, as a comprehensive university, the intake of international students has indirectly given a positive impact especially in terms of the offered programs that fulfil the career prospects of international students. The results has also found that the background factor of University Malaysia Sabah that has a credible and experienced line of lecturers, either locals or academic expatriates, has strengthened the cause of decision to expatriate here and to gain meaningful experiences while studying overseas. Hopefully, the path of this exploration research can be beneficial as well as playing the role in giving a better illustration related to first year expatriation experiences of international students.